Kinetic modeling of hydrogen production rate by photoautotrophic cyanobacterium A. variabilis ATCC 29413 as a function of both CO2 concentration and oxygen production rate - Salleh S.F.; Kamaruddin A.; Uzir M.H.; Mohamed A.R.; Shamsuddin A.H. (Taylor and Francis Inc., 2023)
carbon dioxide; hydrogen; oxygen; Anabaena; kinetics; metabolism; Anabaena; Carbon Dioxide; Hydrogen; Kinetics; Oxygen